2017
DOI: 10.1080/09669582.2017.1310867
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Sustainability and the authentic experience. Harnessing brand heritage – a study from Japan

Abstract: His primary research interests focus on nonprofit marketing and volunteer management practices, as well as areas of authenticity and heritage in tourist consumption. His recent work is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 106 publications
7
34
0
Order By: Relevance
“…Our findings link the different approaches of authenticity found in literature (Taheri et al, 2017). The 'object' is not just a physical object.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our findings link the different approaches of authenticity found in literature (Taheri et al, 2017). The 'object' is not just a physical object.…”
Section: Discussionsupporting
confidence: 83%
“…But if there is such a relationship, the distinction between essential and peripheral features helps suppliers to understand which features are key to generate a consumer experience of authenticity. Consumers may have difficulty to fully express which features are essential for authenticity, and executives may have their own professional bias, so teaming up to determine the essential and the peripheral features definitely helps to define a relevant set of features: negotiated authenticity (Adams, 1996;Taheri et al, 2017 ). Zeng et al (2012) observed how this can be done within a single company: determine the features and, in case of different outlets, replicate these.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-hoc analysis of the indirect effects was carried out. To test for mediation, Taheri, Farrington, Curran, and O'Gorman's (2017) two-step bootstrapping technique was followed. 95% confidence interval (CI) was achieved through bootstrapping.…”
Section: [Figure 2 Here]mentioning
confidence: 99%
“…As presented in Table 4, the study results of the analysis provide empirical support for all of the hypotheses for the Chinese data. Moreover, the analysis of the indirect effects with the bootstrapping method, recommended by Williams and MacKinnon (2008) and Taheri et al (2017) (Table 5) was used. Self-accountability indirectly influences characterological self-blame through CP (CI: .13-.18).…”
Section: Results Of Phase 5: Analysis Of Measurement and Structural Mmentioning
confidence: 99%